2018
DOI: 10.1038/s41598-017-18367-x
|View full text |Cite
|
Sign up to set email alerts
|

A Gaussian extension for Diffraction Enhanced Imaging

Abstract: Unlike conventional x-ray attenuation one of the advantages of phase contrast x-ray imaging is its capability of extracting useful physical properties of the sample. In particular the possibility to obtain information from small angle scattering about unresolvable structures with sub-pixel resolution sensitivity has drawn attention for both medical and material science applications. We report on a novel algorithm for the analyzer based x-ray phase contrast imaging modality, which allows the robust separation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 63 publications
0
23
0
Order By: Relevance
“…Since, from a medical point of view it is desirable to minimize the radiation dose, the authors in [ 6 ] acquired just two images (at roughly half the maximum peak intensity on each side of the RC) and used relative changes of intensity and the slope to compute the two parameters. Assuming a Gaussian RC shape, Arfelli et al [ 19 ] introduced the G 2 DEI algorithm to additionally extract the scattering width from three images on the RC. Chen et al [ 20 ] indicated how to retrieve different types of information from the analysis of the moments of RCs, in particular the skewness (3rd moment) and the kurtosis (4th moment), revealing the asymmetry (caused by the local curvature of interfaces) and the strength of the tails relative to the peak, respectively.…”
Section: Diffraction Enhanced Imagingmentioning
confidence: 99%
See 2 more Smart Citations
“…Since, from a medical point of view it is desirable to minimize the radiation dose, the authors in [ 6 ] acquired just two images (at roughly half the maximum peak intensity on each side of the RC) and used relative changes of intensity and the slope to compute the two parameters. Assuming a Gaussian RC shape, Arfelli et al [ 19 ] introduced the G 2 DEI algorithm to additionally extract the scattering width from three images on the RC. Chen et al [ 20 ] indicated how to retrieve different types of information from the analysis of the moments of RCs, in particular the skewness (3rd moment) and the kurtosis (4th moment), revealing the asymmetry (caused by the local curvature of interfaces) and the strength of the tails relative to the peak, respectively.…”
Section: Diffraction Enhanced Imagingmentioning
confidence: 99%
“…As a reference, we implemented a fitting procedure based on Gaussian functions (Equation (8)), as suggested, e.g., by Arfelli et al [ 19 ]: where I B is the baseline level (offset), θ c is the center, A is the integral, and w the FWHM of the RC for each pixel. The FWHM is linked to the standard deviation σ by the factor (8 ln(2)) ½ .…”
Section: Image Analysis Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…RCs can be modelled using a Taylor series, Gaussian distribution or a Pearson VII function (Pearson, 1916), allowing phase retrieval to be performed. Gaussian functions are commonly used to fit the RCs as they are relatively easy to implement and accurately models the bell curve shape (Zhifeng et al, 2007;Hu et al, 2008;Diemoz et al, 2010;Arfelli et al, 2018). However, Gaussian functions can fail at accurately modelling the peak and tails of the RC from the long slit geometry of ABPCI (Oltulu et al, 2003;Nesterets et al, 2006).…”
Section: Abpci Phase Retrievalmentioning
confidence: 99%
“…Another candidate to extend the value of clinical CT is dark-field imaging which allows to simultaneously measure the attenuation, refraction, and small-angle scattering of a transmitted sample [2]- [4]. While this can be achieved with various methods at synchrotrons (e.g., analyzer-based, speckle-based, propagation-based imaging [5]- [7]) only grating-based Talbot-Lau interferometry and edge illumination have successfully been translated to incoherent X-ray sources with a large source spot [8]- [11].…”
Section: Introductionmentioning
confidence: 99%